2012
DOI: 10.1111/j.1469-0691.2011.03650.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the normalization of CD4+ T-cell count, percentage and CD4+/CD8+ T-cell ratio in HIV-infected patients on long-term suppressive antiretroviral therapy

Abstract: We evaluated factors associated with normalization of the absolute CD4+ T-cell counts, per cent CD4+ T cells and CD4+/CD8+ T-cell ratio. A multicentre observational study was carried out in patients with sustained HIV-RNA <50 copies/mL. Outcomes were: CD4-count >500/mm(3) and multiple T-cell marker recovery (MTMR), defined as CD4+ T cells >500/mm(3) plus%CD4 T cells >29%plus CD4+/CD8+ T-cell ratio >1. Kaplan-Meier survival analysis and Cox regression analyses to predict odds for achieving outcomes were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
53
3
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 36 publications
11
53
3
4
Order By: Relevance
“…In this study, we first demonstrated that the HIV-positive subjects, after 6 months of HAART, experienced significant decreases in viral loads and 0.4-to 3-fold increases in CD4 ϩ /CD8 ϩ T cell ratios. These findings were expected and were consistent with previous studies that showed inverse correlation of CD4 ϩ /CD8 ϩ T cell ra- tios with antiretroviral therapy (51)(52)(53). As the particular focus of the present study, the microbial analysis data showed differences in oral microbial colonization among HIV-seronegative subjects, HIV-seropositive subjects before HAART, and HIV-seropositive subjects 6 months after HAART.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we first demonstrated that the HIV-positive subjects, after 6 months of HAART, experienced significant decreases in viral loads and 0.4-to 3-fold increases in CD4 ϩ /CD8 ϩ T cell ratios. These findings were expected and were consistent with previous studies that showed inverse correlation of CD4 ϩ /CD8 ϩ T cell ra- tios with antiretroviral therapy (51)(52)(53). As the particular focus of the present study, the microbial analysis data showed differences in oral microbial colonization among HIV-seronegative subjects, HIV-seropositive subjects before HAART, and HIV-seropositive subjects 6 months after HAART.…”
Section: Discussionsupporting
confidence: 93%
“…We also investigated the potential association of neutralization breadth with the CD4 ϩ /CD8 ϩ ratio. It has been suggested that the cutoff ratio of Ͻ1.0 is associated with immunosenescence and mortality (47)(48)(49). We therefore evaluated the levels of neutralization breadth (number of subtypes crossed) in patients with CD4 ϩ /CD8 ϩ ratios of Ͻ1 and Ն1.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…A reduction greater than 30% is considered positive. response in patients with healthy CD4 ϩ /CD8 ϩ ratios (Ն1) (47)(48)(49), within the first year of HIV infection, and with patients with lower ratios. Neutralization breadth was significantly higher in patients with CD4 ϩ /CD8 ϩ ratios similar to those of healthy individuals.…”
Section: Figmentioning
confidence: 99%
“…In the general population, a low CD4/ CD8 ratio is considered a surrogate marker of immunosenescence, and has been associated with persistent cytomegalovirus replication and with all-cause mortality. 19e22 In untreated HIV infection, the CD4/CD8 ratio has been investigated as a predictor of poor prognosis, 23e26 and has shown to independently predict immune restoration, 24 AIDS-related 25 and non-AIDS-related morbidities. 26 However, after several years of treatment, some patients still show an inverted ratio despite the normalization of CD4 counts, and the clinical and biological significance of this finding remains unknown.…”
Section: Introductionmentioning
confidence: 99%